Antioxidant and antityrosinase activities of piper maingayi HK. essential oil - Hashim, Nur Athirah; Ahmad, Farediah; Darnis, Deny Susanti (Universiti Teknologi Malaysia, 2016)
The study was aimed to investigate the chemical components of stem and fruit volatile oils of Piper. maingayi Hk. with their antioxidant and antityrosinase activities. GC and GC-MS analysis of the essential oils obtained from the fresh stem and fruit of P. maingayi Hk. resulted in the identification of 34 and 18 components accounting for 83.6% and 78.7% of the total amount, respectively. Sesquiterpene hydrocarbons and oxygenated sesquiterpenes were the most highly represented classes as the former ranging from 64.7% to 70.7%, and the latter varying from 7.4% to 8.6%. The main constituents of the stem oil were: β-caryophyllene (26.2%), -cedrene (8.4%), caryophyllene oxide (6.7%) and cis-calamenene (6.2%), while the fruit oil was dominated by δ-cadinene (22.6%), β-caryophyllene (18.8%), -copaene (11.2%) and -cadinol (7.1%). The stem and fruit of P. maingayi oils showed significant value for antioxidant and antityrosinase activities.